2016
DOI: 10.1097/fbp.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketamine administration, alone and in combination with E-6837, on climbing behavior

Abstract: Some types of schizophrenia have been associated with repetitive movements lacking specific purpose, also known as stereotyped behavior. Dopamine agonists (D2) and noncompetitive N-methyl-D-aspartate receptor antagonists (e.g. ketamine) have been administered in rodent models to induce stereotyped behavior that resembles some motor symptoms of schizophrenia. Recently, a relationship has been found between 5-HT6 receptors (5-HT6Rs) and dopaminergic activity. The present study evaluates the effect of ketamine (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(28 reference statements)
1
4
0
Order By: Relevance
“…The current study found that KET increases scaling behavior, as reported previously, which was reversed by the acute injection of the 5-HT 6 agonist E-6837 (Briones-Aranda et al , 2016). Surprisingly, the antagonist SB-271046 also diminished the scaling behavior (current study).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The current study found that KET increases scaling behavior, as reported previously, which was reversed by the acute injection of the 5-HT 6 agonist E-6837 (Briones-Aranda et al , 2016). Surprisingly, the antagonist SB-271046 also diminished the scaling behavior (current study).…”
Section: Discussionsupporting
confidence: 90%
“…In this sense, it is known that oral administration of the 5-HT 6 R agonists WAY-181187 or WAY-208466 induces a reduction of adjunctive drinking in the rat schedule-induced polydipsia, a phenomenon linked to a reduction in OCB (Schechter et al , 2008). In the same line, our group reported that the 5-HT 6 R agonist E-6837 decreases the scaling behavior of mice tested in the CT after being subjected to a subchronic KET regimen (Briones-Aranda et al , 2016). However, the 5-HT 6 R antagonist DNA-1184 decreases the OCB in the marble-burying test (MBT) (Partyka et al , 2016).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition, IN administration showed a significant reduction in the crossed-squares number compared to the IV ZP solution ( p < 0.05). This improvement in antipsychotic activity could be correlated with the selective increase in glutamate and dopamine release in the prefrontal cortex, nucleus accumbens and striatum [ 53 , 54 ]. ZP may inhibit the 5-HT2A receptors on glutamatergic terminals, causing a spontaneous reduction in the stimulating effect of ketamine in the dopamine-glutamate pathway [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ketamine dose affects the animals' behavior as a result of its effect on the neurotransmitters. Ketamine-induced hyperlocomotion was produced by a selective increase in glutamate and dopamine release in the prefrontal cortex, nucleus accumbens and striatum [62,63]. Pretreated rats with OZ solution or OZ-PM with a dose of 2 mg/kg showed a significant decrease in the ketamine-induced hypermobility, which was indicated by decreases in the observed rats' mobility (p < 0.001).…”
Section: Open Field Testmentioning
confidence: 95%